KONSELING MULTIKULTURAL: UPAYA PREVENTIF BULLYING PADA LESBIAN DI MASYARAKAT DAN SEKOLAH - Nurintan Muliani Harahap; Amril Maryolo (Institut Agama Islam Negeri Palopo, 2018)
The objectives achieved in this paper are to neutralize cases of bullying that occur in minority groups, especially lesbians in communities and schools using multicultural counseling. In general, people consider lesbians as sinners, sexual deviations and sexual disorders, not infrequently these groups experience discrimination and stigma. The problem faced by this sexual orientation or gender identity requires empathy and sensitivity so that problems can be solved. One of the problems experienced by LGBT especially lesbians is bullying. Forms of intimidation from the nearest person or from others, logging, the exclusion of his friends commonly referred to as bullying behavior. In order for such cases to be unsustainable there needs to be a handling so that minority groups can move in accordance with their respective potential.